Fast detection of E. coli with a novel fluorescent biosensor based on a FRET system between UCNPs and GO@Fe3O4 in urine specimens. Issue 19 (27th April 2021) - Yao, Yuan; Xie, Guoming; Zhang, Xin; Yuan, Jinshan; Hou, Yulei; Chen, Hui
Abstract : As detection signal, UCNP fluorescence could improve the detection ability of the biosensor in complex biological samples. UCNPs unbound to bacteria could be separated by magnet, improving the sensitivity and detection time of the biosensor. Abstract : Biosensors based on nanomaterials are becoming a research hotspot for the rapid detection of pathogenic bacteria. Herein, a "turn-on" fluorescent biosensor based on a FRET system was constructed for the fast detection of a representative pathogenic microorganism, namely, E. coli, which causes most urinary tract infections. This biosensor was constructed by utilizing synthesized UCNPs as fluorescent donors with stable luminescence performance in complex biological samples and GO@Fe3 O4 as a receptor with both excellent adsorption ability and fluorescence quenching ability. A specific ssDNA selected as an aptamer which could recognize E. coli was immobilized on the UCNPs to form UCNP-Apt nanoprobes. The nanoprobes were adsorbed on the surface of GO@Fe3 O4 through the π-stacking interactions between aptamers and GO. In the presence of E. coli, UCNP-Apt nanoprobes detached from GO@Fe3 O4 due to the specific recognition of aptamers and bacteria, resulting in obvious fluorescence recovery, and the concentration of bacteria was positively correlated with the intensity of the fluorescence signal; such a "turn-on" signal output mode ensures excellent precision. In addition, the easy magnetic separation of GO@Fe3 O4 simplifies the operation process, helping the sensor detect bacteria in 30 minutes with a linear range from 10 3 to 10 7 CFU mL −1 and a limit of detection of 467 CFU mL −1 . Moreover, recovery test results also showed that the sensor has clinical application potential for the rapid detection of pathogenic microorganisms in complex biological samples.